Ethical issues and strategies for the voluntary participation of children in research - Siqueira Sigaud, Cecilia Helena de (2009)
Ethical issues about research with human beings have been addressed in health literature since decades. In spite of this, it is necessary to enhance actions to face many challenges, like the ones related to investigation of childhood. This paper presents and discusses ethical issues in research with children. It describes some strategies to perform with children, considering their developmental process and individual characteristics, in order to guarantee their voluntary participation in research.